2015
DOI: 10.1007/s13224-015-0783-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Uterine Prolapse Cases in South India

Abstract: Background Uterine prolapse is a common problem among women in developing countries. It is known to cause physical and psychosocial problems affecting the quality of life of patients. This study was done to determine the risk factors, clinical features, and management practices in uterine prolapse (UP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Women with short birth intervals are associated with higher maternal mortality [19]. However, limited studies have been done on the relationship between short birth interval and the occurrence of POP [20,21]. Therefore, preventive efforts can be suggested if the interval between each birth relates to the occurrence of POP.…”
Section: Introductionmentioning
confidence: 99%
“…Women with short birth intervals are associated with higher maternal mortality [19]. However, limited studies have been done on the relationship between short birth interval and the occurrence of POP [20,21]. Therefore, preventive efforts can be suggested if the interval between each birth relates to the occurrence of POP.…”
Section: Introductionmentioning
confidence: 99%
“…There is study showed that greater BMI was a significant risk factor for POP [11]. However, another study analyzed the BMI as a continuous variable showed that higher BMI was a protective factor for POP [17]. Theoretically, there is chronic intraabdominal pressure increase in obese women which causes excessive load on the pelvic structures, including the pelvic floor muscles, fascia, and pudendal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, there is chronic intraabdominal pressure increase in obese women which causes excessive load on the pelvic structures, including the pelvic floor muscles, fascia, and pudendal nerves. In addition, people who are obese generally have comorbidities such as diabetes which also contribute to poor tissue quality, and are more likely to experience symptoms of lower urinary tract syndrome (LUTS) such as urinary incontinence [16], [17]. A study also found that weight loss was not significantly associated with improvement in POP, thereby that the damage to the pelvic floor caused by weight gain was irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pelvic floor dysfunctions in India is 21%, which is higher and not far away from the USA (25%) [ 35 ]. Risk factors for pelvic floor dysfunctions are vaginal mode of delivery [ 36 ], multiparity [ 37 ], lower-class economic group [ 5 ], progression in age [ 38 , 39 ], and so on.…”
Section: Discussionmentioning
confidence: 99%